Human Monocyte-Derived Suppressor Cell Supernatant Induces Immunoregulatory Effects and Mitigates xenoGvHD - Gérard, Claire; Thébault, Marine; Lamarthée, Baptiste; Genet, Coraline; Cattin, Florine; Brazdova, Andréa; Janikashvili, Nona; Cladière, Claudie; Ciudad, Marion; Ouandji, Séthi; Ghesquière, Thibault; Greigert, Hélène; et al. (Frontiers in Immunology, 2022)
Recently developed cell-based therapies have shown potential for graft-versus-host disease (GvHD) mitigation. Our team previously developed a protocol to generate human monocyte-derived suppressor Cells (HuMoSC), a subpopulation of CD33+ suppressor cells of monocytic origin. CD33+HuMoSC successfully reduced xenoGvHD severity in NOD/SCID/IL-2Rγc-/- (NSG) mice. While CD33+ HuMoSC culture supernatant inhibits T cell activation and proliferation, the recovery of CD33+ HuMoSC immunosuppressive cells and the subsequent production of their supernatant is limited. An attractive solution would be to use both the CD33+ and the large number of CD14+ cells derived from our protocol. Here, we assessed the immunoregulatory properties of the CD14+HuMoSC supernatant and demonstrated that it inhibited both CD4 and CD8 T cell proliferation and decreased CD8 cytotoxicity. In vivo, injection of CD14+HuMoSC supernatant reduced xenoGvHD in NSG mice. Furthermore, CD14+HuMoSC supernatant maintained its immunoregulatory properties in an inflammatory environment. Proteomic and multiplex analyses revealed the presence of immunosuppressive proteins such as GPNMB, galectin-3 and IL-1R(A) Finally, CD14+HuMoSC supernatant can be produced using good manufacturing practices and be used as complement to current immunosuppressive drugs. CD14+HuMoSC supernatant is thus a promising therapy for preventing GvHD.